(untitled) (Research, Society and Development, 2021)
Given the complexity of the etiopathogenesis of the diseases that affect the periodontium, several mechanisms to support conventional periodontal therapy, based on non-surgical and surgical steps have been studied in the literature, including ozone in its various vehicles and with various purposes. The aim of this study was to describe the applications of ozone therapy in Periodontology, in the areas of surgical and non-surgical therapy from the viewpoint of molecular, cellular and tissue effects focused on the repair process. An integrative literature review was conducted using the Pubmed/MEDLINE and SciELO databases with the search terms ozone, periodontal disease and periodontal surgery associated with the Boolean operator and. After applying the eligibility criteria listed by the PRISMA-ScR strategy, 15 articles were selected for qualitative analysis in order to answer the following study question, developed by the PICO strategy: "What are the advantages of ozone therapy in periodontics from the microbiological, cellular and tissue repair points of view? It is perceived that ozone is a good adjunct to conventional periodontal therapy, due to its hemostatic, angiogenic, analgesic, anti-hypoxic and antimicrobial effects, in addition to impacts on the molecular signaling pathways of the inflammatory response, Although further studies are needed so that protocols for its application can be standardized based on clinical practice based on scientific evidence, given the potential for improvement in tissue repair and consequently in periodontal surgical recovery time, which unfolds to the quality of life of patients affected by periodontitis.